Analysis of the Influence of Migration on Poverty in Indonesia - Ibnu Hajar; Okta Maula Misena; Romi Bhakti Hartarto (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2025)
Alleviating poverty and creating prosperity is the ultimate goal for every country, especially in developing countries. The Indonesian Government initiates various poverty alleviation efforts, one of which is the transmigration program. As a strategic plan to reduce poverty, it is necessary to pay special attention to the results of migration activities. This study aims to determine the effect of migration on poverty rates in Indonesia. This study uses pooled cross-sectional data analysis for 34 Indonesian provinces in 2015 and 2019 using the Ordinary Least Squares model. Based on this research, it was found that permanent in-migration did not affect poverty, but there was a positive and significant effect of permanent out-migration and rising out-migration on poverty. Meanwhile, in-migration has a negative and significant effect on poverty. Another finding from this study is that wages and education have a negative and significant effect on poverty, while the place of origin does not affect poverty.  Keywords: Indonesia, in-migration, out-migration, poverty JEL: A11, A1